Private banking customers' preferences of delivering channels of products in South Africa - Ramoliko, Khathutshelo (My University, 2016)
This study sought to establish private banking customers’ preferences between receiving contact with a relationship manager and contact via digital channels when interacting with the bank in general and when they made use of various products and services offered by the bank. A literature review of relationship marketing, the use of digital platforms in banking and customer interaction was conducted. A survey sample of 183 private banking customers who made use of relationship managers was used to establish their preferences between the two channels when performing banking activities. Private banking customers are increasingly self-directed and prefer digital contact for many of the services provided by a bank. A comprehensive analysis of private banking customers’ preferences between face-to-face and digital channels was conducted across various banking services. Lastly, the implications of these outcomes for the private banking industry are proposed and discussed.
MBA
Keywords: Banks and banking -- South Africa. Consumers' preferences -- South Africa. Relationship marketing -- South Africa.Mobile commerce -- South Africa.